Re-Making Places: HCI, 'Community Building' and Change - Crivellaro, Clara; Taylor, Alex; Vlachokyriakos, Vasillis; Comber, Rob; Nissen, Bettina; Wright, Peter (CHI '16 Proceedings of the 2016 CHI Conference on Human Factors in Computing Systems, 2016)
Clara Crivellaro, Alex S Taylor, Vasillis Vlachokyriakos, Rob Comber, Bettina Nissen, Peter Wright (2016) Re-Making Places: HCI, 'Community Building' and Change, CHI '16, p. 2958-2969, New York: ACM Press, pdf, doi:10.1145/2858036.2858332 We present insights from an extended engagement and design intervention at an urban regeneration site in SE Lon-don. We describe the process of designing a walking trail and system for recording and playing back place-specific stories for those living and working on the housing estate, and show how this is set within a wider context of urban renewal, social/affordable housing and "community building". Like prior work, the research reveals the frictions that arise in participatory engagements with heterogeneous actors. Here we illustrate how material interventions can re-arrange existing spatial configurations, making productive the plurality of accounts intrinsic in community life. Through this, we provide an orientation to HCI and design interventions that are concerned with civic engagement and participation in processes of making places.